Sustainable energy simulation for water heating system - Hujailan, Faleh F.F.; Maleque, Md. Abdul; Rahman, M. M.; Bello, K. A. (University of Nigeria, Nsukka, 2021)
There is a tremendous demand of renewable energy use as a source of sustainable energy in buildings and other applications due to environmental protection, elimination of the use of fossil fuels, and reduction of greenhouse gas emissions. A technically attractive solution for effective water heating system in buildings has received a great attention in recent years and has been a major focus. Therefore, the aim of this work is to study a water heating system in building using sustainable solar energy. The building-integrated solar water heater system is designed and rendered using Sketch Up to meet the requirement of the occupants. The thermal performance of building-integrated solar water heating system was evaluated based on the calculation using T*SOL Pro 5.5 (R11) simulation software which is a dedicated software for solar thermal heating system. The economic feasibility was also carried out for solar water heating system with the design parameters. The results of the evaluation showed that the maximum annual energy output was 1,599.5 kWh/m2 with the efficiency of 35% for flat plate collector design system. The economic analysis also showed that flat plate collector is a cost-effective design for the solar water heater system due to its steadiness and lower maintenance cost. Keywords: Sustainable energy, Water heating system, Thermal efficiency; Flat plate collector; Economic analysis.